Pakistan Studies : An Investigation Into The Political Economy 1948-1988 - Nadeem Qasir (Karachi Oxford University Press, 1991)
This is an in-depth study of the inter-relationship of sociology, politics and economics in Pakistan.
Includes Index
Keywords: Pakistan -- Politics and Government